Enforceability of digital copyright on the darknet? - Mathini, Moses Wanjukia (Intellectual Property Research Unit, 2018)
This dissertation seeks to comparatively analyse different emerging jurisprudence of pioneering jurisdictions on the operability of enforcing digital copyright in light of the growing use of the Darknet. It addresses the legal lacuna in the existing copyright laws with regards to enforcement against the illegal distribution of infringing copies of online digital content. It also seeks to illustrate how the concept of digital copyright protection has been compromised by the inoperability of enforcement laws on illegal distribution via the Darknet. It thereby advocates for a 'digital use' exemption and or free access as a recommendation. Although the advancement of technology created new and advanced forms of distribution or availing copyrighted works to the public, these new advanced channels of distribution have been compromised by rogue online clandestine file sharing networks. Digital copyright protection laws have been advanced so as to respond to illegal online file sharing, however, they have had limited impact due to the vast, flexible and unregulated nature of the internet which transcends the territorial nature of any single state's copyright laws. Currently, online file sharing is effected through peer to peer networks due to their operational convenience. This dissertation suggests that the need to control distribution, legally or technological, is driven by the urge to enable digital copyright owners to benefit financially from their works and get a return on their investment. Technologically, this has been effected through the adoption of Digital Rights Management (DRMs) measures that control access to these works through the use of paywalls on commercial websites that require online consumers to pay/ subscribe first before they gain access to the copyrighted works. (eg Netflix, Showmax, itunes e.t.c) However, since absolute control over one's digital works, online, is impossible, the success of these access-control mechanisms remains debatable and remain vulnerable to technologically sophisticated users who could easily circumvent them and make the protected works available to millions of other users in Darknets. This, in effect, creates a parallel and free market for digital content. Darknets have grown as the new preferred channel of distribution due to their unique features which have rendered any judicial or legislative threat of sanctions, merely academic and detached from practical application. The Darknet essentially provides for user privacy, in anonymity, and security from monitoring and detection. These two primary features have exacerbated online piracy as various Darknets ISPs have now developed more user-friendly Darknet versions for the average mainstream user. This dissertation will highlight how the digital creative industry faces an existential threat with the growing use of Darknets. Darknets have created a virtual environment where illegal digital content distribution continues with impunity, since the burden of the enforceability of copyright rests squarely on the individual copyright holder and the pursuit of liability only begins upon detection of any such infringement of copyright. In effect, copyright owners, most often than not, lack the technological expertise to monitor and detect and thereby cannot enforce their copyright. As such, this dissertation postulates that the legal/ technological effort to maintain any form of monopoly over digital content online is an unattainable objective. As a solution, to end both online piracy and safeguarding the financial interests of copyright owners, a change in the approach to digital copyright is needed. This will be achieved through creating a 'digital use' exemption and or free access. Rather than copyright owners trying to control access, they should provide free access and profit on alternative revenue business models. Free access to digital content will do away with the need of online users to pirate and also save copyright owners the effort and resource to keep monitoring the virtual world for infringement. It will also counter-react to the Darknet's parallel market since users will have free access to digital content from the official distribution websites. This dissertation will interrogate the viability of this option.